Evaluation of the expected doses of fire brigades at the Chornobyl Exclusion Zone in April 2015 - V. A. Kashparov; M. A. Zhurba; S. I. Kireev; S. V. Zibtsev; V. V. Myroniuk (Ядерна фізика та енергетика)
Assessment is given of area and behavior of large wildfire in the Chornobyl Exclusion Zone (ChEZ) which has been burning during April 27 - 29, 2015. Levels of radionuclide contamination of combustible material show that expected effective dose of firefighters during one fire-line hour did not exceed 0.64 μSv in case of external exposure and 0.37 μSv in case of internal exposure. It is shown that the expected effective dose of internal exposure of firefighters during suppression of wildfires in ChEZ was below the dose from external exposure. At the moment exposures of 90Sr and 241Pu (along with 238-240Pu and 241Am) make the most significant contribution to the internal dose of firefighters during forest and grassland fires suppression in the ChEZ.